Menstrual Hygiene Education among Student Girls of Elementary School at SDN 47 Korong Gadang, Padang - Yessy Markolinda; Ice Yolanda Putri (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM) Universitas Andalas, 2024)
The research conducted by UNICEF in Indonesia in 2020 revealed that one in five girls is unaware of menstrual hygiene management. Taboos and stigma also limit the activities of female students during menstruation. Menstrual Hygiene Management (MHM) is the method of maintaining cleanliness and health for women during their menstrual cycle. The Ministry of Health is improving menstrual hygiene by implementing three aspects in the School Health Effort (Trias UKS), including health education, health services, and a healthy school environment. Community service activities were conducted at the Elementary School of SDN 47 Korong Gadang, Padang City, on 3 June 2022. The number of participants was 30 students from the 4th and 5th grades. Education was delivered through lectures and discussions, supported by visual aids such as slides and leaflets. The evaluation used pretests and post-tests to determine whether there was an improvement in students' knowledge. After the education session, it was found that 60% of the students had acquired a high level of knowledge regarding menstrual hygiene management. The results of this community service can serve as a lesson that education related to personal hygiene during menstruation is crucial. It is because some female students, while menstruating, experience bullying from male students and encounter obstacles in practicing menstrual hygiene at school.